Developing Students' Spiritual Intelligence Through Religious Practices at Muhammadiyah Plus Junior High School In Salatiga - Ulfa Dwi Lestari; Purnomo Purnomo (UMSU, 2026)
The development of students' spiritual intelligence is an important requirement in education to face the challenges of modernity and overcome the decline in the moral character of students. In response to this, this study aims to analyze the religious habit formation program at Muhammadiyah Plus Junior High School in Salatiga and examine it from the perspective of spiritual intelligence development. This study uses a qualitative approach with a case study type, using interview, observation, and documentation. Data analysis in this study was conducted using the Miles Huberman and Saldana analysis model, which includes data collection, data condensation, data display, and conclusion drawing. The research results obtained in developing spiritual intelligence are in the form of religious habituation through daily, weekly and semester habituation programs. This process is reinforced by teacher role models, school culture habits, and the involvement of all stakeholders. The impact of this program is seen in the improvement of students' religious-social attitudes, such as responsibility, independence, discipline, and social concern.